Thermal Transport in Combined Sutterby-Casson-Micropolar Flow via Exponential Curvature: A Regression-Based Numerical Study (European Journal of Pure and Applied Mathematics, 2026)
We studied the flow of Sutterby–Casson micropolar fluid over an exponentially stretching curved sheet, including the effects of Soret and Dufour phenomena. A low Reynolds number magnetic field is considered to analyze its impact on the flow. The mathematical model is developed using boundary layer approximations, resulting in a system of partial differential equations (PDEs) based on relevant flow assumptions. These PDEs are then converted into ordinary differential equations (ODEs) via similarity transformations. The resulting ODEs are solved numerically. The results are presented with both graphs and tables, emphasizing how key physical parameters affect the flow behavior. Significant changes in the values of D1 and C1 indicate that the primary independent variable affecting heat and mass transfer shifts its behavior between n = 0.0 and n = 0.5. The large negative values of D6 and C6 suggest a dominant opposing factor within thesystem. When comparing n = 0.0 and n = 0.5, the system demonstrates a decreased sensitivity to changes in the independent variables. Additionally, the value of n influences heat and mass transfer mechanisms differently, which correspond to varying flow conditions and thermal properties.
Keywords: Soret and Dufour effects; Sutterby Casson micropolar fluid; Regression and Numerical analysis